Proyek Pemasaran Digital di Sosial Media dan E- Commerce Melalui Pembuatan Content Marketing dan Advertising Campaign Untuk Meningkatkan Brand Awareness Racabel - Randi Saputra; Faizal Adiprasetya Purnama Pulungan (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This study aims to analyze the digital marketing strategies implemented by Racabel, a local fashion accessories brand, to enhance brand awareness through social media and e-commerce platforms. The project includes creating marketing content and paid advertising campaigns across platforms such as Instagram, TikTok, Shopee, and Tokopedia. The strategy focused on content optimization to strengthen audience interaction and increase engagement on social media. The results of these campaigns show a significant increase in followers, engagement rates, and sales conversions on marketplace platforms. With the right content optimization and measurable advertising strategies, Racabel successfully expanded its market reach and improved brand awareness among the target audience.